(untitled) (International Journal of Islamic Business, 2019)
Islamic Banking has become competitive against conventional banking since it is one of the fastest growing institutions nowadays. Therefore, it is reasonable to expect that the performance of both Islamic and conventional banks has become the center of attention particularly in term of their profitability. Hence, the purpose of this study is to investigate the relationship between bank-specific characteristics and profitability of Islamic and conventional in Malaysian banking sector to find the role of internal factors in achieving high profitability from 2008 to 2016. The data is extracted from Fitch Connect database for a nine year period which includes 16 Islamic banks and 22 conventional banks in Malaysia. The findings explained that each variable are justified in the model have statistically significant impacts on Malaysian banks’ profitability. However, the effects are not uniform across profitability measures. Regression findings reveal that bank capital and deposit ratio are significant of bank profitability in Islamic banks. This result implying that high profitability may drive higher capital ratios since profits are a source of capital. The implication shows that a more profitable bank may desire a smaller capital buffer since it knows that it will be able to draw on internal funds to fund expected investment opportunities.